The Development of Administration and Government Regulations During the Time of Umar bin Khattab - Usdarisman Usdarisman; Meirison Meirison; Abdul Basit; Nissa Aldani (JETL (Journal of Education, Teaching and Learning), 2025)
When Umar ibn al-Khattab succeeded Abu Bakr al-Siddiq, the Muslim armies continued their advance, conquering Persia, Syria, and Egypt, which were part of the Roman Empire. The spoils of war increased, and Umar faced new problems in dispatching supplies, organizing troops, and governing the conquered lands. As Muslims conquered more and more new territories, problems would arise from various dimensions of life. We reanalyze Umar ibn al-Khattab's actions in dealing with administrative governance issues, such as the placement of employees and governors and the allocation of finances. We approach this by heuristically collecting sources, verifying, analyzing, and explaining them descriptively. Ijtihad was one of the most prominent aspects of Umar's life during his phenomenal, eventful caliphate. He guarded and preserved the faith of the Muslims, raised the banner of jihad, conquered new lands, and spread Justice to all Muslim and non-Muslim communities. He established the first Ministry of Finance in Islam, formed a regular army to defend and protect the borders, arranged salaries and supplies, documentation, state archives, appointed governors, workers, and judges, and approved the currency for daily circulation. He was a multidimensional administrator and legal interpreter